Teacher intervention strategies in the task of reading to complete questionnaires - Rosli, Natalia (2017)
Considering the epistemic potential of reading and writing as instruments of thought and development of new knowledge, this article focuses on disciplinary teaching in high school courses with the help of reading and writing. Its main objective is to describe and analyze intervention strategies used by three Argentinean teachers in a recurrent task: reading to answer questionnaires. We found no studies addressing teaching mediated by reading and writing in subjects with students from low-income families. This qualitative naturalistic case study was conducted in last-year courses attended mostly by students who work and are adolescent parents. In-depth interviews were conducted with three teachers and fourteen students, 39 classes were observed and class-material was collected. Data were analyzed using categorization and contextualization strategies. Results show that teachers perform three functions: definition of the environment, environmental management, and evaluation of the task. These functions install students on task but do not tend to explore how they interpret the texts. The structure of the activity could be redefined in order to promote epistemic uses of reading, writing and dialogue as well as to allow interpretations to be expressed and discussed in class. This would offer students the opportunity of accessing, communicating and reflecting on disciplinary contents. We claim that the epistemic use of these tools can ultimately contribute with educational equity